Talking Down Pain in the Prosthesis Clinic: The Emergence of a Local Preference. Issue 1 (2nd January 2022) - Galatolo, Renata; Fasulo, Alessandra
ABSTRACT: Understanding and evaluating pain is a growing concern in clinical practice and health care. In this article we examine how pain is talked about in 24 video-recorded visits of a team of medical professionals with postsurgery amputees. We identify a paradox: Although it is medically useful to identify postamputation pain (it can indicate problematic healing and deter application of a prosthesis), we found that there was a joint preference, by both patients and professionals, to minimize pain sensations. We show how both parties draw on turn design, sequential organization, and multimodal resources to acknowledge some kinds of unpleasant sensations while excluding types of pain that would be problematic in view of the prosthesis. We discuss the importance of the findings in terms of furthering the understanding of situated expression and reporting of pain, the emergence of local preferences in clinical settings, and preference organization in general. Data are in Italian.